Public accounting profession and fraud detection responsibility. Issue 2 (2nd November 2020) - Rustiarini, Ni Wayan; Yuesti, Anik; Gama, Agus Wahyudi Salasa
Abstract : Purpose: The study aims to examine the influence of auditor personal factors, such as goal orientation, self-efficacy and professional commitment to auditor's responsibility to detect the fraudulent, particularly in small accounting firms. Design/methodology/approach: The authors surveyed 86 auditors working in small accounting firms in Bali Province, Indonesia. Findings: The results prove the role of self-efficacy as a mediating variable in the relationship of goal orientation and auditor responsibility. This result at once confirms that self-efficacy can improve individual performance even in complex tasks. This study also proves the role of professional commitment as a mediator variable. Research limitations/implications: Given that the respondents came from small accounting firms, these findings are not intended to be generalized with auditors in large accounting firms. Practical implications: These findings highlight essential efforts to reduce audit expectation gaps between auditors and the public. The small accounting firms' leaders must to alignment workplace organizational goals and organization professional goals. A dualism of purpose causes the auditor to fail to fulfill the responsibility of fraud detection. Social implications: There is a severe audit expectation gap related to the auditor's role in detecting fraud. This finding expected to answer public questions related to auditors' ability and responsibility in small accounting firms in detecting fraud. Originality/value: There is limited research on auditor responsibility, particularly in small audit firms in developing countries. Also, there is still debate scientific about the influence of goal orientation, self-efficacy and professional commitment to auditor performance.